2020
DOI: 10.1021/acs.langmuir.9b03333
|View full text |Cite
|
Sign up to set email alerts
|

Diffusiophoresis in Multivalent Electrolytes

Abstract: Diffusiophoresis is the spontaneous movement of colloidal particles in a concentration gradient of solutes. As a small-scale phenomenon that harnesses energy from concentration gradients, diffusiophoresis may prove useful for passively manipulating particles in lab-on-a-chip applications as well as configurations involving interfaces. Though naturally occurring ions are often multivalent, experimental studies of diffusiophoresis have been mostly limited to monovalent electrolytes. In this work, we investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
57
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 35 publications
2
57
0
3
Order By: Relevance
“…2020; Wilson et al. 2020; Alessio et al. 2021), a dead-end pore configuration is used to set up a transient one-dimensional (1-D) diffusion of solutes; significant colloidal dispersion is observed, which the typical models are unable to capture.…”
Section: Introductionmentioning
confidence: 99%
“…2020; Wilson et al. 2020; Alessio et al. 2021), a dead-end pore configuration is used to set up a transient one-dimensional (1-D) diffusion of solutes; significant colloidal dispersion is observed, which the typical models are unable to capture.…”
Section: Introductionmentioning
confidence: 99%
“…To my knowledge, the existing phenomena that have been discussed in the above context pertain to binary electrolytes or assume one-dimensional gradients [6,[19][20][21][22][23]. In this Letter, I argue that a still further enriched phenomenology arises in multicomponent electrolytes when concentration gradients are superimposed in different directions ("crossed" salt gradients).…”
mentioning
confidence: 86%
“…Diffusiophoresis is the spontaneous motion of colloidal particles under a solute concentration gradient. Since the first recognition 1,2 , the phenomenon has been widely studied theoretically and experimentally [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . When the solute is an electrolyte, the net motion of particles has electrophoretic and chemiphoretic contributions, induced by, respectively, the diffusivity difference(s) among the ions and the osmotic pressure gradient near the particle surface 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Various experimental investigations have been reported for the diffusiophoresis of micron-sized particles, either in the presence or absence of liquid flow [12][13][14][18][19][20][21][22] . Recently, it has been demonstrated that dissolution of gas can drive diffusiophoresis of charged particles [22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%